Childhood and Adolescents Sleep Bruxism Treatment: A Systematic Review - Senff, Jordana; Bonotto, Danielle Veiga; Hilgenberg-Sydney, Priscila Brenner; Sebastiani, Aline; Scariot, Rafaela; Oda, Lisa Yurie (Sleep Science, 2023)
Introduction Sleep Bruxism (SB) is a common condition in childhood that can cause multiple consequences such as abnormal tooth wear, tensional headaches, masticatory muscle pain, or fatigue. The literature reports some interventions, however the treatment for SB in children is not well-established.Objectives A systematic review was performed to investigate the effectiveness of the treatments described for SB in children and adolescents: pharmacological and psychological treatments; behavioral guidelines; and dental approaches.Materials and methods Randomized clinical trials comparing different SB treatments with a control group were searched in the electronic databases PubMed, Scopus, Web of Science, Cochrane Library, and VHL until August 04, 2021. Two independent reviewers selected the studies, extracted the data, and assessed the risk of bias. After a two-phase selection process, 07 articles were selected. The methodology of the selected studies was analyzed using the Cochrane Risk of Bias Tool. The criteria used to qualify the studies were based on randomization, allocation, blinding of participants and evaluators, and analysis of results.Results The signs and symptoms of SB were reduced with pharmacotherapy (hydroxyzine/diazepam) and medicinal extracts (M. Officinalis), but with occlusal splints and physiotherapy, this improvement was not statistically significant when compared to control groups.Conclusion Some evidence of the efficacy of pharmacotherapy (hydroxyzine/diazepam) and medicinal extracts (M. Officinalis) was found. However, this systematic review is not enough to establish a protocol for the treatment of SB. Besides, the individualized management of SB in this population should be considered, emphasizing the management of risk factors.
Keywords: bruxism; sleep bruxism; treatment; systematic review